A bottom-up approach to study the moisture susceptibility of bio-modified asphalt. (30th December 2020) - Oldham, Daniel J.; Fini, Elham H.
Highlights: The passivation mechanism of bio-modified asphalt contributes to enhanced resistance to moisture damage. Bio-modifiers molecules occupy active sites of silica oxide. Bio-modifiers prevent nucleation and growth of acidic compounds at the bitumen-silica interface. Binders doped with amide and amine functional groups show improved adhesion to siliceous aggregates. Abstract: Causes and remedies for moisture damage at the interface of binder and siliceous stone aggregates is not fully understood and is considered as one of the most elusive and intractable pavement distresses. In recent years, increasing environmental awareness and decreasing availability of virgin materials have promoted the use of bio-materials to decrease adverse environmental impacts from petroleum-based products and support sustainable practices. Considering source dependency and composition variation in bio-materials, it is important to relate composition to fundamental materials properties in order to ensure adequate overall performance particularly in terms of resistance to moisture. Therefore, the current study uses a bottom-up approach to evaluate the performance of an asphalt binder additive from swine manure (Bio-modifier) as a means of not only improving but also understanding moisture resistance in asphalt pavement. Bio-modification was found to show improved moisture resistance at the binder level and the mixture level when compared to two other commercially available additives. Further analysis of the binder doped with representative molecules of the additives showed varying differences in adhesion and moisture susceptibility. To provide in-depth understanding of the underlying interaction mechanisms between water and binder, molecular dynamic simulations were performed on a blend of asphaltene and dopant molecules placed on a silica oxide substrate and exposed to water molecules. Study results revealed the passivation mechanism of bio-modifiers as a dominant factor contributing to enhanced resistance to moisture damage. It was found that bio-modifiers molecules occupy active sites of silica oxide preventing nucleation and growth of acidic compounds at the binder-silica interface. Such acidic compounds are water soluble and their presence at the interface can be detrimental leading to moisture damage. Study results showed anchored bio-modifiers molecules further interact with asphaltene molecules to provide bridging mechanism between binder and silica. This in turn leads to enhanced resistance to moisture damage in bio-modified binders adhered to siliceous surfaces such as quartz and granite stone aggregates.